Evaluation and driving factors analysis of agricultural green development level in Beijing from 1978 to 2022 - Liang, Lina; Huai, Heju; Tang, Xiumei (Frontiers in Ecology and Evolution, 2023)
Agricultural green development (AGD) plays an important role in achieving a sustainable society. This paper evaluates the AGD level of Beijing from 1978 to 2022 by means of a comprehensive evaluation method, coupling coordination degree (CCD), and grey relational degree model (GRA) with the purpose of exploring relevant stages and characteristics, as well as analyzing the characteristics of different stages and the coupling relationship of various factors and quantitatively calculating the driving factors for AGD change. The results showed that: 1) the AGD level of Beijing generally improved from 1978 to 2022, mainly involving four stages of steady rising, fluctuating, oscillating decreasing, and rapid upgrading; 2) the CCD of the development subsystems of AGD, agricultural resource utilization, agricultural environment conditions, agricultural industry development, and farmers’ living standard, all rose and the coordination type of each subsystem gradually went through a verge imbalance stage, reluctantly coordinated stage, and primary coordinated stage to an intermediate coordinated stage, and then reached a well-coordinated stage in 2019; 3) the AGD level of Beijing is influenced by economic development, the industrial structure, urbanization, technological progress, and agricultural structure. Finally, some policy suggestions to promote AGD in Beijing are put forward. This paper is of great significance to promoting the green and sustainable development of agriculture in Beijing and provides technical support and policy guidance for AGD in other regions.